COUNTER DISCOURSE ON MENTAL HEALTH ISSUES IN GENERATION Z ON TWITTER - Loho, Pieter Wilson; Isnaini, Muhamad (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This research is motivated by the massive issue of mental health on social media, especially Twitter. Generation Z is the party most stigmatized for mental health issues. This research seeks to answer how discourse develops regarding mental health issues among generation Z on Twitter. This research uses a qualitative approach with virtual ethnographic methods. Generation Z netizens' conversations on Twitter were recorded using cloud-based software Netlytic. The research results show the diversity of discourse on mental health issues. This discourse shows that generation Z displays a counter strategy, namely leaving the dominant discourse on mental health. This counter-discourse arose because so far mental health has always been associated with dictions such as depression, anxiety, stress, and even suicide. To find a solution to this threatening diction, they create a new discursive strategy by saying that mental health is nothing more than a matter of religiosity, espoused values, or seeking professional help.